2001
DOI: 10.1159/000056901
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant DNA copy number amplification at 17q and 22q in dermatofibrosarcoma protuberans

Abstract: Dermatofibrosarcoma protuberans (DFSP) is a tumor of low or intermediate malignant potential with a tendency for recurrence, but low rate of metastasis. The tumorigenesis of DFSP has recently been shown to be associated with the fusion of the collagen type I alpha 1 (COL1A1) and platelet-derived growth factor B-chain (PDGFB) genes, often as a consequence of translocation t(17;22)(q22;q13). Cytogenetically, DFSP is often characterized by supernumerary ring chromosomes containing material from chromosomes 17 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 10 publications
3
25
0
Order By: Relevance
“…Our data also confirm the trend noted by Kiuru-Kuhlefelt, who used CGH to find a small increase in copy number changes of chromosome 17 and 22 material in a study set of similar size to our present study. 13 Their data did not reach statistical significance and this finding not only reflects the difficulty CGH would have in detecting subtle changes of copy number but also that combining together cases that operate with and without gains of COL1A1-PDGFB in a nonpaired analysis may obscure individual tumor oncogenic mechanisms. The use of fluorescence in situ hybridization allows for individual cases and individual areas to be compared, and counting signals allows for fine differentiation in trends and the exclusion of normal cells such as blood vessels, adipocytes or inflammatory cells by morphologic examination during the counting process.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our data also confirm the trend noted by Kiuru-Kuhlefelt, who used CGH to find a small increase in copy number changes of chromosome 17 and 22 material in a study set of similar size to our present study. 13 Their data did not reach statistical significance and this finding not only reflects the difficulty CGH would have in detecting subtle changes of copy number but also that combining together cases that operate with and without gains of COL1A1-PDGFB in a nonpaired analysis may obscure individual tumor oncogenic mechanisms. The use of fluorescence in situ hybridization allows for individual cases and individual areas to be compared, and counting signals allows for fine differentiation in trends and the exclusion of normal cells such as blood vessels, adipocytes or inflammatory cells by morphologic examination during the counting process.…”
Section: Discussionmentioning
confidence: 97%
“…12 However, a single previous study was not able to find a difference in copy numbers between fibrosarcomatous and dermatofibrosarcoma protuberans areas using comparative genomic hybridization. 13 The objective of our study was to evaluate whether genomic gains of the COL1A1-PDGFB fusion gene occur during the clonal evolution of dermatofibrosarcoma protuberans into fibrosarcomatous dermatofibrosarcoma protuberans using fluorescence in situ hybridization. In addition, we aimed to determine if there was a difference between the number of COL1A1-PDGFB gene fusion copies between cases of classic dermatofibrosarcoma protuberans and dermatofibrosarcoma protuberans areas associated with fibrosarcomatous transformation.…”
mentioning
confidence: 99%
“…Our results were confirmed by similar results obtained in some CGH-based studies, which showed the t(17;22) translocation is usually associated with increased copy numbers of the COL1A1 and PDGFB genes. [8][9][10]27 Interestingly, of the 42 tumor samples analyzed, three showed a deletion; in two of these three samples, the amplification levels were lower than that of the paired normal tissue. These cases were suggested to have unbalanced translocations instead of the supernumerary ring chromosome.…”
Section: Pdgfb and Pdgfrb Mrna Expressionmentioning
confidence: 99%
“…We selected the albumin gene located at 4q11-q13 as the reference gene because no genetic alteration has been detected in this chromosomal region, as determined by CGH studies. [8][9][10] PCR was performed using the ABI Prism 7700 Sequence Detection System (Applied Biosystems) according to the manufacturer's protocol. The PDGFB gene copy numbers were calculated from the standard curve constructed from normal DNA amplification.…”
Section: Evaluation Of the Pdgfb Gene Amplification Levelmentioning
confidence: 99%
“…The etiology of DFSP remains unclear and may be associated with certain genetic characteristics, a history of trauma and the extent of radiation exposure. Recent studies on the molecular basis of DFSP development have reported that >90% of DFSP patients present with the t(17;22)(q22;q13.1) chromosomal translocation, which causes the fusion of the collagen type 1 α1 chain (COL1A1) gene on 17q22 and the platelet-derived growth factor β chain (PDGFB) gene on 22q13.1 (7)(8)(9)(10). This results in the formation of the COL1A1-PDGFB fusion protein.…”
Section: Dermatofibrosarcoma Protuberans With Pit-like Lesionsmentioning
confidence: 99%